Pengaruh Pajak Hotel, Pajak Restoran, Pajak Parkir, dan Retribusi Pelayanan Persampahan/Kebersihan terhadap Pendapatan Asli Daerah (PAD) Kota Yogyakarta Tahun 2022-2024 - Aulia Puji Rahayu; David Sulistiyantoro (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2026)
This study is motivated by the importance of optimizing regional revenue sources to support sustainable regional development. Yogyakarta City, as one of Indonesia’s main tourist destinations, has significant potential to increase Regional Original Revenue (PAD) through hotel tax, restaurant tax, parking tax, and waste management service retribution. However, the realization of regional tax revenues has shown fluctuations, influenced by taxpayer compliance and suboptimal management. This research aims to analyze the effect of hotel tax, restaurant tax, parking tax, and waste service retribution on the PAD of Yogyakarta City from 2022 to 2024. A quantitative approach was applied using documentation methods and secondary time-series data. The findings indicate that hotel tax has a negative effect on PAD, while restaurant tax has a positive effect on PAD. Parking tax and waste management/cleanliness service retribution show insignificant effects on PAD. Simultaneously, all independent variables have a significant effect on PAD. This study contributes to the understanding of how local taxes and levies impact regional income and provides useful insights for local governments in formulating tax and retribution policies to optimize regional revenue in Yogyakarta City.